2011
DOI: 10.1158/1541-7786.mcr-11-0018
|View full text |Cite
|
Sign up to set email alerts
|

Quiescin Sulfhydryl Oxidase 1 Promotes Invasion of Pancreatic Tumor Cells Mediated by Matrix Metalloproteinases

Abstract: Quiescin sulfhydryl oxidase 1 (QSOX1) oxidizes sulfhydryl groups to form disulfide bonds in proteins. We previously mapped a peptide in plasma from pancreatic ductal adenocarcinoma (PDA) patients back to an overexpressed QSOX1 parent protein. In addition to overexpression in pancreatic cancer cell lines, 29 of 37 patients diagnosed with PDA expressed QSOX1 protein in tumor cells, but QSOX1 was not detected in normal adjacent tissues or in a transformed, but nontumorigenic cell line. To begin to evaluate the ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 29 publications
7
63
0
Order By: Relevance
“…Model for QSOX1-mediated tumor cell invasion. QSOX1 activates matrix metalloproteinases (MMPs) that are capable of digesting basement membranes (46) and incorporates laminin into fibroblasts, which facilitates the migration of tumor cells into the fibroblast layer (44). The production of H 2 O 2 by QSOX1 may also elicit vascular endothelial growth factor (VEGF) production by tumor cells, stimulating blood vessel growth into the tumor (62).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Model for QSOX1-mediated tumor cell invasion. QSOX1 activates matrix metalloproteinases (MMPs) that are capable of digesting basement membranes (46) and incorporates laminin into fibroblasts, which facilitates the migration of tumor cells into the fibroblast layer (44). The production of H 2 O 2 by QSOX1 may also elicit vascular endothelial growth factor (VEGF) production by tumor cells, stimulating blood vessel growth into the tumor (62).…”
Section: Resultsmentioning
confidence: 99%
“…In 2011 and 2013, we reported that QSOX1 plays a role in pancreatic and breast tumor cell growth and invasion in vitro (46,47). We also demonstrated that QSOX1 affects the proteolytic activity of matrix metalloproteins (MMP-2 and -9) FIG.…”
Section: Tumor Biology Of Qsox1mentioning
confidence: 86%
See 1 more Smart Citation
“…The biological function of QSOX1 is to oxidate sulfhydryl members during protein folding to generate disulfide bonds in proteins, thus ultimately reducing the transformation from oxygen to hydrogen peroxide [8,9,10]. Recently, QSOX1 has been identified over-expressed in pancreatic and breast cancers and plays an important role in pancreatic and breast cancer cells invasion via activating MMP-2 and MMP-9 [11,12,13,14]. However, the regulation mechanism of QSOX1 remains largely elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In MM cells, inhibition of HSP90 by 17-AAG results in cell cycle arrest and apoptosis (31). Quiescin sulfhydryl oxidase 1 (QSOX1) is involved in protecting cells from ROS induced apoptosis by preserving mitochondrial polarity (32) and in the activation of matrix metalloproteinases (MMP) 2 and 9 (33).…”
Section: Between-experiments Data Evaluation (A) Principal Componenmentioning
confidence: 99%